2007
DOI: 10.1111/j.1095-8649.2006.01293.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect of osmotic concentration, potassium and pH on motility of the sperm of the North American burbot Lota lota maculosa

Abstract: Seminal plasma factors maintaining North American (NA) burbot Lota lota maculosa sperm quiescent were examined. Sperm were diluted into buffered saline solutions of various compositions and motility assessed. After 1 h in these solutions at 10°C, aliquots of the suspension were diluted with tap water and motility again assessed. Dilution of sperm in an incubation solution containing Ca 2þ in the absence of K þ initiated sperm motility resulting in low motility when sperm were subsequently diluted in tap water.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 26 publications
0
18
0
Order By: Relevance
“…In the present study, composition of L. lota seminal fluid was approximately similar to that reported in previous studies on L. lota (Lahnsteiner et al ., ; Dziewulska & Pilarska, ) and slightly differ from the composition of L. l. maculosa seminal fluid (Zuccarelli et al ., ). Based on our results, spontaneous activation of motility appeared at 20°C and maximum motility was recorded at 30°C (Table ), which was outside the temperature range (>5°C) reported by Lahnsteiner et al .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the present study, composition of L. lota seminal fluid was approximately similar to that reported in previous studies on L. lota (Lahnsteiner et al ., ; Dziewulska & Pilarska, ) and slightly differ from the composition of L. l. maculosa seminal fluid (Zuccarelli et al ., ). Based on our results, spontaneous activation of motility appeared at 20°C and maximum motility was recorded at 30°C (Table ), which was outside the temperature range (>5°C) reported by Lahnsteiner et al .…”
Section: Discussionmentioning
confidence: 99%
“…Zuccarelli et al . () demonstrated that a combination of high K + level, high osmolality and, probably, high pH is involved in keeping sperm in the quiescent state in seminal fluid in the L. l. maculosa . It has also been suggested that Ca 2+ plays a key role in the initiation of motility with a dose dependent response in L. l. maculosa sperm (Zuccarelli et al ., ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Motility of sperm was assessed within 5 sec of dilution of semen (41:1000; Woolsey et al, 2006) or following 60 min incubation (1:100) at 201C with subsequent dilution in tap water (1:10) following modified methods of Zuccarelli et al (2007). Fraction of total sperm demonstrating motility was assessed from sequential images captured 1 sec apart using the software Motic Images 2000 1.3 (Motic Incorporation Ltd., Hong Kong, China) in conjunction with a National DC3-163 microscope with digital camera (National Optical & Scientific Instruments Inc., San Antonio, TX).…”
Section: Evaluation Of Sperm Motilitymentioning
confidence: 99%
“…tap water), the range of specific factors that maintain sperm quiescent in seminal plasma, before spawning, are not well established (Morisawa and Suzuki,'80;Morisawa et al,'83b,'91;Morisawa and Morisawa,'90;Lahnsteiner et al,'97). For example, in the Salmonidae, sperm are maintained immotile within seminal plasma by high K '91; Toth et al, '97;Alavi et al, 2004a,b;Lahnsteiner et al, 2004) as well as a freshwater gadid (Zuccarelli et al, 2007) are maintained immotile predominately by K 1 and osmolality and sperm of the Cyprinidae are maintained immotile solely by osmolality (Morisawa et al, '83c;Marian et al, '93;Krasznai et al, 2000Krasznai et al, , 2003aLinhart et al, 2003). Although carp and salmonid sperm are maintained in seminal plasma, cytoplasmic Ca 21 is maintained at low levels (Okuno and Morisawa, '89;Krasznai et al, 2000).…”
mentioning
confidence: 97%